2018
DOI: 10.3389/fphar.2018.01077
|View full text |Cite
|
Sign up to set email alerts
|

28-Day Oral Chronic Toxicity Study of Arctigenin in Rats

Abstract: Arctium lappa (burdock) is the most popular daily edible vegetable in China and Japan because of its general health tonic effects. Previous studies focused on the beneficial role of Arctigenin but neglected its potential side-effects and toxicities. In the present study, the sub-chronic toxicity profile of Arctigenin following 28 days of consecutive exposure was investigated in rats. The results showed that during the drug exposure period, Arctigenin-12 mg/kg administration resulted in focal necrosis and lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 43 publications
2
17
0
1
Order By: Relevance
“…In addition, we did not determine the most effective dose and safe dose range of ATG. Previous studies showed the least observed adverse effect was induced by 12 mg/kg daily ATG exposure for successive 28 days in rats (Tan et al, 2018). In the present study, no mortality and obvious clinical signs of ATG-related toxicity were observed in animals treated with ATG (3 mg/kg/d) alone during the study period (28 days, data shown in Supplementary Figure S1), suggesting that ATG may be safe to treat PQ-induced fibrosis.…”
Section: Discussionsupporting
confidence: 63%
“…In addition, we did not determine the most effective dose and safe dose range of ATG. Previous studies showed the least observed adverse effect was induced by 12 mg/kg daily ATG exposure for successive 28 days in rats (Tan et al, 2018). In the present study, no mortality and obvious clinical signs of ATG-related toxicity were observed in animals treated with ATG (3 mg/kg/d) alone during the study period (28 days, data shown in Supplementary Figure S1), suggesting that ATG may be safe to treat PQ-induced fibrosis.…”
Section: Discussionsupporting
confidence: 63%
“…Accordingly, the liver is chosen due to its vital role in organism being reflected by its physiological functions, synthesis and detoxification of various metabolites. In other words, any lesions caused by drugs, chemicals, and pathological status could interrupt its functions [27]. The ALT level, which is found primarily in the liver, and is released into the circulation from damaged hepatocytes, was slightly higher in the experimental group, while the AST level, found in the erythrocytes, myocytes, and kidney cells also, was higher in the control, without significant differences [27].…”
Section: Discussionmentioning
confidence: 98%
“…In other words, any lesions caused by drugs, chemicals, and pathological status could interrupt its functions [27]. The ALT level, which is found primarily in the liver, and is released into the circulation from damaged hepatocytes, was slightly higher in the experimental group, while the AST level, found in the erythrocytes, myocytes, and kidney cells also, was higher in the control, without significant differences [27]. Similar results of biocompatibility investigation of Mg-Zn materials were reported, with the assertion that there was no change in the hepatocyte architecture and morphology of liver lobules [28].…”
Section: Discussionmentioning
confidence: 99%
“…The hematopoietic system is considered to be the most sensitive target for toxicities, and its index of physiological and pathological status is direct evidence for toxicology studies (32). Hematological analysis data suggested that, except for the WBC, NE and PLT counts, other hematological parameters showed no toxicologically significant differences.…”
Section: Discussionmentioning
confidence: 99%